Characterization of a multipurpose NS3 surface patch coordinating HCV replicase assembly and virion morphogenesis - Isken, Olaf; Pham, Minh Tu; Schwanke, Hella; Schlotthauer, Felicia; Bartenschlager, Ralf; Tautz, Norbert (PLoS pathogens, 2022)
The hepatitis C virus (HCV) life cycle is highly regulated and characterized by a step-wise succession of interactions between viral and host cell proteins resulting in the assembly of macromolecular complexes, which catalyse genome replication and/or virus production. Non-structural (NS) protein 3, comprising a protease and a helicase domain, is involved in orchestrating these processes by undergoing protein interactions in a temporal fashion. Recently, we identified a multifunctional NS3 protease surface patch promoting pivotal protein-protein interactions required for early steps of the HCV life cycle, including NS3-mediated NS2 protease activation and interactions required for replicase assembly. In this work, we extend this knowledge by identifying further NS3 surface determinants important for NS5A hyperphosphorylation, replicase assembly or virion morphogenesis, which map to protease and helicase domain and form a contiguous NS3 surface area. Functional interrogation led to the identification of phylogenetically conserved amino acid positions exerting a critical function in virion production without affecting RNA replication. These findings illustrate that NS3 uses a multipurpose protein surface to orchestrate the step-wise assembly of functionally distinct multiprotein complexes. Taken together, our data provide a basis to dissect the temporal formation of viral multiprotein complexes required for the individual steps of the HCV life cycle. Author summary HCV genome replication and virion morphogenesis take place in dedicated cellular membrane compartments that serve as assembly sites of specialized protein complexes executing these processes. Maturation of these macromolecular protein complexes requires a step-wise succession of protein-protein interactions that must be tightly controlled in a spatio-temporal manner to avoid the formation of non-functional protein complexes. NS3 has a pivotal role in this temporal regulation by providing multipurpose surface areas for the assembly of functionally distinct protein complexes. By interrogating these NS3 surface areas, we show that a set of phylogenetically conserved NS3 residues forms a continuous surface patch across protease and helicase domain that is critical for NS5A hyperphosphorylation, a feature shown to be important for replicase formation to support HCV RNA replication. Furthermore, a helicase residue in close proximity to these residues is pivotal for virion morphogenesis without affecting genome replication. We propose that NS3 provides distinct surface areas to regulate, in a temporal and spatial fashion, the assembly of various, dedicated protein complexes during the different steps of the hepaciviral life cycle that are crucial for replicase assembly and virion formation.
Gesehen am 31.03.2023